PENDIDIKAN DAN PELATIHAN MODEL ASSESSMEN KOMPETENSI MINIMAL (AKM) UNTUK MENINGKATKAN PROFESIONALISNE GURU MATA PELAJARAN BAHASA SUNDA DI KABUPATEN PANGANDARAN - Kuswari, Usep; Rahman, Rahman; Haerudin, Dingding; Nugraha, Haris Santosa; Hernawan, Hernawan; Sutisna, Ade (Dimasatra, 2023)
The target of the results of this service program is expected that this training will be carried out as an effort to improve the professionalism of Sundanese language teachers in Pangandaran Regency in understanding, implementing, and developing Minimal Competency Assessment (AKM) models in Sundanese language subjects. The subjects are Sundanese language teachers in junior high and high school levels in Pangandaran Regency. The activity carried out is a training activity to prepare Sundanese language teachers in facing the digital era and global competition. Pangandaran Regency was chosen as a training location because its area is quite far from the city center of West Java, so that Sundanese language teachers there must also be given the same training to deal with this development. This training requires an increase in teacher professionalism in applying the AKM model in accordance with the demands of the current application of learning policies. The output targets of this training are (1) scientific articles published in national journals (2) scientific articles presented in international seminars, and (3) draft Intellectual Property Rights (IPR)